Biophilic Design: Psychological and Physiological Health and Well-being - Ryan, Catherine O.; Clancy, Joseph; Browning, William (urbanNext, 2018)
Biophilic design can reduce stress, enhance creativity and clarity of thought, improve our well-being and expedite healing; as the world population continues to urbanize, these qualities are ever more important. Theorists, research scientists, and design practitioners have been working for decades to define aspects of nature that most impact our satisfaction with the built environment. (3z(B14 Patterns of Biophilic Design(3y (Barticulates the relationships between nature, human biology and the design of the built environment so that we may experience the human benefits of biophilia in our design applications.s
Catherine Ryan, Energy and sustainability, Essay, expanding design practices, Joseph Clancy, Low Density, William Browning
Architecture&nature, Comfortable environment, Design, Design strategies, Designer$1 (Bs role, Essay, Health, Natural connectors, Nature, Psychological Well-being, Public space role, Space, Spatial patterns, Urban environment, Urban Health, Water, Well-beings
Excerpt from "14 Patterns of Biophilic Design" published by Terrapin Bright Green.
Keywords: Biophilic Design; Health